Od sztuki do życia i z powrotem. Wizyta Prousta w Jeu de Paume - Renzi, Lorenzo (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article is an attempt at analysing the biographical episode which inclined Proust to rework Bergotte’s death in In Search of Lost Time. Renzi shows how literature (or more generally: art) and life intertwine. By analysing fragments of Proust’s famous novel as well as his records and letters, the author presents the French writer as an avid fan of Vermeer’s paintings. He also touches upon the history of the influence of the Dutch painter on Proust’s works.